2010
DOI: 10.4314/just.v30i2.60536
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Control Strategy for Monitoring the Delaminating Damage in Drilling Of Carbon Composite Laminates

Abstract: Composite materials have attractive features, such as high strength to weight ratio and high stiffness to weight ratio. However, they are easily damaged during machining operations. A typical damage is delamination, which can occur when fiber reinforced composite laminates are drilled. Control of delamination is critical for the utilization of composite materials. This research seeks to develop a technique to control inter-ply delaminations during the drilling of laminated composites. A statistical factorial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this case, it was pointed out that AE could be used in order to monitor damage to the tool and the treated surface. The strategy of applying AE to control a technological process of drilling the composite is examined in [5]. The algorithm for strategy implementation is based on the fact of relationship between the AE energy and the parameters of technological process.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In this case, it was pointed out that AE could be used in order to monitor damage to the tool and the treated surface. The strategy of applying AE to control a technological process of drilling the composite is examined in [5]. The algorithm for strategy implementation is based on the fact of relationship between the AE energy and the parameters of technological process.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It is also revealed that the relation between the delamination area, the feed rate and the cutting speed is given as A d = Kƒ α t b (Andoh, 2005), where K, α and β are constants and depend on the material used. These constants need to be studied together with the drilling time at onset of delamination instead of the remaining drilling time (Andoh et al, 2010). An on-line technique may also account for the anisotropic nature of the material.…”
Section: Introductionmentioning
confidence: 99%